PENGARUH EPS, DER, PER, ROA DAN ROE TERHADAP HARGA SAHAM PADA PERUSAHAAN TAMBANG YANG TERDAFTAR DI BEI UNTUK PERIODE 2011-2013 - Hilmi Abdullah; Soedjatmiko -; Antung Hartati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract,This research aims to prove empirically whether EPS, DER, PER, ROA, and ROE affect stock prices on mining companies listing on the Indonesia Stock Exchange Period 2011-2013.This research method using quantitative methods. The population in this research is a mining company listed on the Indonesia Stock Exchange (BEI) in 2011-2013 amounted to 20 companies. The sampling technique used in this research is purposive sampling. Samples were selected by 13 companies.The results of the research hypothesis testing is partially explained DER affect the stock prices of mining companies in Indonesia Stock Exchange 2011-2013, while the EPS, PER, ROA, and ROE does not affect the stock prices of mining companies in Indonesia Stock Exchange 2011-2013. The results of hypothesis testing simultaneously EPS, DER, PER, ROA, and ROE affect stock prices of mining companies in Indonesia Stock Exchange 2011-2013.